Pharmacological effects of Astragalus polysaccharides in treating neurodegenerative diseases - Shi, Yuanshu; Ma, Ping (Frontiers in Pharmacology, 2024)
Astragalus membranaceus（AM）, widely used in traditional Chinese medicine, exhibits multiple pharmacological effects, including immune stimulation, antioxidation, hepatoprotection, diuresis, antidiabetes, anticancer, and expectorant properties. Its main bioactive compounds include flavonoids, triterpene saponins, and polysaccharides. Astragalus polysaccharides (APS), one of its primary bioactive components, have been shown to possess a variety of pharmacological activities, such as antioxidant, immunomodulatory, anti-inflammatory, antitumor, antidiabetic, antiviral, hepatoprotective, anti-atherosclerotic, hematopoietic, and neuroprotective effects. This review provides a comprehensive summary of the molecular mechanisms and therapeutic effects of APS in treating neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), and multiple sclerosis (MS). It discusses how APS improve insulin resistance, reduce blood glucose levels, enhance cognitive function, and reduce Aβ accumulation and neuronal apoptosis by modulating various pathways such as Nrf2, JAK/STAT, Toll, and IMD. For PD, APS protect neurons and stabilize mitochondrial function by inhibiting ROS production and promoting autophagy through the PI3K/AKT/mTOR pathway. APS also reduce oxidative stress and neurotoxicity induced by 6-hydroxydopamine, showcasing their neuroprotective effects. In MS, APS alleviate symptoms by suppressing T cell proliferation and reducing pro-inflammatory cytokine expression via the PD-1/PD-Ls pathway. APS promote myelin regeneration by activating the Sonic hedgehog signaling pathway and fostering the differentiation of neural stem cells into oligodendrocytes. This article emphasizes the significant antioxidant, anti-inflammatory, immunomodulatory, and neuroprotective pharmacological activities of APS, highlighting their potential as promising candidates for the treatment of neurodegenerative diseases.